PENGARUH SUHU DAN LAMA DISTILASI TERHADAP RENDEMEN DAN KARAKTERISTIK CUKA FERMENTASI DARI CAIRAN PULPA HASIL SAMPING FERMENTASI BIJI KAKAO - Wiji Astuti, Ni Kadek; Ganda Putra, Gusti Putu; Semadi Antara, Nyoman (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2015)
Pulp liquid waste is the by-product produced during process of cacao bean fermentation. This liquid contains acetic acid which could be utilized as vinegar. Distillation method can be done to recover the acid as cacao vinegar. In present work, the experiment was done to determine the effect of distillation temperature and time on the yield and characteristics of cacao vinegar recovered from liquid waste of cacao fermentation. The experiment was designed by randomized block design with two factors of experiment, namely temperature and time of distillation. The first factor was the distillation temperature (S) which consists of two levels, i.e 90°C and 100°C. The second factor was the distillation time (W) which consists of five levels, i.e 30, 60, 90, 120, 150 minutes. The best characteristic of cacao vinegar was examined by the test of effectiveness. The interaction of temperature and time of distillation affected significantly the yield of vinegar, but the interaction did not affect the characteristics of cacao vinegar. However, the single factor of distillation temperature or distillation time significantly affected the yield and the characteristics of vinegar as well. By using effectiveness test the best of cacao vinegar was found on distillation temperature of 90 o C at 150 minute. The yield of cacao vinegar was 22.83% with the total of acid, acetic acid content, pH, alcohol content, and total of soluble solid were 0.0808 mEq NaOH/g, 0.49% (w/w), 2.72, 5.39%, and 4.33 o Brix, respectively.
Keywords: 59